1989
DOI: 10.2527/jas1989.672441x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Digestibility of Nitrogen and Amino Acids in Protein Feedstuffs by Growing Pigs

Abstract: Eight digestion trials were conducted with pigs fitted with ileal T-cannulas to determine the apparent digestibilities of N and amino acids in common protein feedstuffs. Trial-to-trial variation was minimal as determined by the variation in digestibilities for soybean meal, which was evaluated in each trial. Apparent digestibilities varied widely; ileal N digestibility ranged from 88 to 63%, and ileal lysine digestibility ranged from 93 to 40%. In general, ring-dried blood meal, corn gluten meal, Menhaden fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
95
7
20

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(148 citation statements)
references
References 0 publications
19
95
7
20
Order By: Relevance
“…The nutritive value of meat and bone meal is mainly dependent on raw material composition and processing conditions (Just et al 1982, Haugen et al 1985, Batterham et al 1986, Knabe et al 1989, Bruyer et al 1990, Skilton et al 1991. The chemical composition of the MBM sample analyzed in the present study (Table 1)is in agreement with the results reported by others (Just et al 1982, Knabe et al 1989, Bruyer et al 1990). Finnish feed tables (Salo et al 1990) give a somewhat lower fat content (90 g CF/kg DM) for meat and bone meal than that measured in the present experiment.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The nutritive value of meat and bone meal is mainly dependent on raw material composition and processing conditions (Just et al 1982, Haugen et al 1985, Batterham et al 1986, Knabe et al 1989, Bruyer et al 1990, Skilton et al 1991. The chemical composition of the MBM sample analyzed in the present study (Table 1)is in agreement with the results reported by others (Just et al 1982, Knabe et al 1989, Bruyer et al 1990). Finnish feed tables (Salo et al 1990) give a somewhat lower fat content (90 g CF/kg DM) for meat and bone meal than that measured in the present experiment.…”
Section: Resultssupporting
confidence: 83%
“…As indicated by several authors (Just et al 1982, Knabe et al 1989, Bruyer et al 1990, Skilton et al 1991, meat and bone meal is not a single product but a variety of different products and, hence, actual nutrient contents and their digestibilities can differ considerably from those given in feed tables. Therefore, reduced performance may result from inappropriate nutrient values being ascribed to the product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent ileal digestibilities of AA in this study (Table 2) are in the range of values for growing pigs fed diets containing fish meal as the sole source of protein (Knabe et al 1989;Wiseman et al 1991). This suggests that the protein in fish meal is easily digested by weanling pigs.…”
Section: Resultsmentioning
confidence: 63%
“…No diarrhea was Knabe et al (1989) and Wiseman et al (1991). The concentration of calcium and phosphorus in the HCaP diets was approximately twice that in the NCaP diets.…”
Section: Resultsmentioning
confidence: 84%